Isolated Fetal Ascites Secondary to Persistent Urogenital Sinus. (12th January 2009) - Camanni, D.; Zaccara, A.; Capitanucci, M. L.; Mosiello, G.; Capolupo, I.; Iacobelli, B. D.; De Gennaro, M.
Abstract : Objective . To present a case of isolated ascites secondary due to urogenital abnormalities (urogenital sinus) without any other prenatal ultrasound marker. Method . A 36-year-old woman with prenatal isolated ascites delivered a female baby, weighing 2.285 g; ascites was drained at birth and the baby underwent several episodes of urinary retention prior to undergoing X-ray investigations. Results . A voiding cystourethrogram revealed a short urogenital sinus: a vesicostomy was performed. A vaginoscopy revealed double vagina with a large posterior vagina. A posterior sagittal anorectal pull-through with genitoplasty was performed at 2 years old with 1-year follow-up. Conclusions . Though rare, a urogenital abnormality is to be suspected in fetal ascites cases with negative viral tests and no cardiac anomalies. The most common ultrasound marker of such abnormalities (fluid filled cavity) may be missing because of complete drainage of urine through the tubes into peritoneum.